2022
DOI: 10.3390/atmos13040529
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in the Concentration of Particulate Matter in the Air of Cracow Affect the Magnitude of CD4+ T Cell Subsets Cytokine Production in Patients with Inflammatory and Autoimmune Disorders

Abstract: Recently, the increased prevalence of chronic civilization diseases triggered by environmental pollution has been observed. In this context, the role of air pollution in the pathogenesis of autoimmune and/or inflammatory disorders is poorly elucidated. Here, we asked whether seasonal changes in the air quality of the city of Cracow affect the polarization of T cell subsets in healthy donors (HD) and patients with rheumatoid arthritis (RA), multiple sclerosis (MS), and atherosclerosis (AS). Peripheral blood mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 70 publications
3
7
0
Order By: Relevance
“…122.6120.261.2015). Basic characterization of the patients and healthy donors (mean age, sex ratio) and the frequencies of the disease’s prevalence in the local population were already documented [ 30 ]. Briefly, data showed that the mean age of patients was 30.88 ± 7.36 for MS, 43.55 ± 10.51 for RA, 69.90 ± 11.02 for AS, and 38.90 ± 11.17 for HD.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…122.6120.261.2015). Basic characterization of the patients and healthy donors (mean age, sex ratio) and the frequencies of the disease’s prevalence in the local population were already documented [ 30 ]. Briefly, data showed that the mean age of patients was 30.88 ± 7.36 for MS, 43.55 ± 10.51 for RA, 69.90 ± 11.02 for AS, and 38.90 ± 11.17 for HD.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, PBMCs after 3 h of culture with or without PM KRK were harvested, washed in PBS (Corning), resuspended in binding buffer, stained with Annexin V-FITC and propidium iodide (PI) (15 min at room temperature), and examined by flow cytometry (FACSCalibur, BD Biosciences Immunocytometry Systems, San Jose, CA, USA). Typically, 10,000 events were acquired for analysis [ 30 ]. On the day of blood collection, the concentration of PM 10 in the air of Krakow, in the summer and winter periods in 2019–2021, was recorded [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations